DESAIN ALAT UJI NOSEL DENGAN MENGGUNAKAN PRINSIP TEROWONGAN ANGIN SUPERSONIK - Jihad, Bagus H; Priadi, Dedi (Indonesian Journal of Aerospace, 2011)
The accuracy of nozzle design can be improved by validation. Two methods of validation is software or hardware application. The software can be either CFD software or special software for the nozzle design, such as NOZZLE ® or Aerospike ®. The limitations of CFD software is on unsteady flow conditions. while the limitations of special software is the obscurity of assumptions used. Therefore, the flow validation experimental is important to be implemented. Lapan has three units of wind tunnels, namely subsonic, transonic and supersonic. They have the capability to measure the external flow of the body. While the nozzle design purpose is mostly to investigate the internal flow of the nozzle. Therefore, the nozzle flow testing system which is called a mini wind tunnel has been designed. This wind tunnel is designed to have speed of Mach 2.4, but the effective speed of 2 Mach. By using a calculation we obtain the run time of 46 seconds. If we assume the pressure drop is 40%, then actually the run time is 28 seconds.